Aplicação data mining para análise e previsão das estratégias de pricing em companhias aéreas. Estudo de caso : registos das tarifas da rota SSA-LIS - Rita, Pedro Artur Alves (2019)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence